The Relationship between CFO Compensation and Corporate Sustainability: An Empirical Examination of German Listed Firms - Mirko Profitlich (MDPI AG, 2021)
In this paper, we analyze the relationship between Chief Financial Officer (CFO) compensation and Corporate Sustainability (CS) by relying on stakeholder-agent theory and institutional theory. Taking a closer look at the German DAX30 and MDAX firms for the business years 2014–2018 (313 firm-year observations), we perform regression and correlation analyses to determine if the different CFO compensation components are related to CS. Our analyses use the environmental, social, governance (ESG) performance as a proxy for CS, determined by the Asset Four database of Thomson Reuters and the CFO compensation data from the Beck et al. (2020) database, and reveal a positive relationship between CS and CFO compensation for pension and stock compensation. Based on our knowledge, this study is the first empirical study that takes a closer look at the relationship between the different CFO compensation components and CS for the German DAX30 and MDAX firms. This result comes with important implications concerning the design of CFO compensation and for future research.